Kanon und Geschichte. Eine Thesenreihe - Nicklas, Tobias (Sacra scripta, 2017)
The relationship between the texts of the Biblical Canon which are believed to be inspired by God’s word and their history of development has been understood as a problem since the days of Enlightenment. The article points to the fact that the history of the Biblical Canon, its texts and their functions in different historical contexts is not just a history of its development. Instead, the “canonical process” goes on until today. It shows that even after the more or less universal recognition of the New Testament canon in late antique churches the weight and impact of different books changed with their interpretation. In addition, even after the fourth century C.E. new extra-canonical writings (like late antique Apostolic narratives, new apocalypses reinterpreting history, time and end-time, texts developing new ideas of the otherworld etc.) developed, answered new questions, filled important spaces of authority which were left open by the canonical writings, and (together with the canonical texts, interpreting or even criticizing them) created landscapes of memory important for many aspects Christian identity formation. All this creates new problems: can writings like these at least in some cases also be called “inspired”? What are the criteria to decide about this question? And what does this mean both for the principle of sola scriptura and a church which understands the study of the Bible as the “soul of theology”?